Program Evaluation of the Monthly Health Review Program: A Strategy to Protect High-Risk Field Workers in the Manufacturing Industry from COVID-19 - Melati Yalti Kautsar Syahrial; Dewi Sumaryani Soemarko; Agus Sugiharto; Nuri Purwito Adi; Boy Subirosa Sabarguna (The Indonesian Journal of Community and Occupational Medicine, 2026)
Background: The Indonesian government has issued guidelines for companies during the COVID-19 pandemic to monitor high-riskemployees due to the severe complications associated with COVID-19. The study aims to identify the cause of program issues and determinepotential improvements to achieve the program’s target of a monthly health review, protecting high-risk field workers in the manufacturingindustry from COVID-19.Methods: A mixed-methods approach combining quantitative and qualitative data was employed, utilizing the Problem-Solving Cycle.Quantitative data were obtained from document reviews, which revealed the characteristics of the Implementers (n=5) and program participants(n=58). Qualitative data are collected through in-depth interviews with policy stakeholders, program implementers, and program participantsto identify the causes of program problems. These problems are then prioritized as main issues using the USG method, and alternative solutionsare discussed. The selected solutions are evaluated based on their effectiveness and efficiency using the Reinke method.Results: On average, 89.58% of participants attended the program throughout the past two years, and only 59.98% of individuals had ahealth condition under control. The interviews revealed that the absence of a Standard Operating Procedure (SOP) was the primary cause ofthe failure to achieve the attendance and under control health condition targets, which were also impacted by a lack of coordination. Nonadherence to medication contributes to discordant comorbidities.Conclusion: Creating an SOP with a relevant target program is the primary solution, and internal meetings to create a monthly schedule.Additionally, the company doctor and program implementers regularly educate program participants to raise awareness of the benefits oftaking the medication regularly.